2002
DOI: 10.1007/s10162-002-2046-6
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Olivocochlear Neurons in the Cat Studied with the Retrograde Tracer Cholera Toxin-B

Abstract: We employed cholera toxin-B (CTB), an ef®cient retrograde tracer, to examine olivocochlear (OC) neurons in the cat. Our primary goals were (1) to determine whether the cat has two types of lateral OC (LOC) neurons as is found in certain rodents and (2) to document the morphology, number, and caudorostral distribution of OC neurons, bilaterally. Adult cats received injections of CTB through the round window of the left cochlea, and, after 3±6 days, the brains were sectioned transversely and CTB was revealed imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Since the ␣9 and ␣10 subunits of the nicotinic acetylcholine receptor are specific for the medial system (Vetter et al, 1999;Lustig, 2006), the blockade by strychnine perfusion would not alter any lateral effects on primary afferents. However, activation of the lateral system by electrical stimulation at the floor of the IVth ventricle has never been confirmed and is considered unlikely in view of the unmyelinated axons of the lateral system (Brown, 1987;Warr et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Since the ␣9 and ␣10 subunits of the nicotinic acetylcholine receptor are specific for the medial system (Vetter et al, 1999;Lustig, 2006), the blockade by strychnine perfusion would not alter any lateral effects on primary afferents. However, activation of the lateral system by electrical stimulation at the floor of the IVth ventricle has never been confirmed and is considered unlikely in view of the unmyelinated axons of the lateral system (Brown, 1987;Warr et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of TH-positive neurons in the LSO is small, it is well known that at least one class of LSO neurons (termed shell neurons, in the rat) travel long distances within the cochlea, project with numerous bifurcations, and end with many terminal boutons. These neurons have been well described in the guinea pig (Brown 1987), rat (Vetter andMugnaini 1992;Warr et al 1997;Warr andBoche 2003), chinchilla (Azeredo et al 1999), and hamster (Sanchez-Gonzalez et al 2003), and may exist in the cat as well (Warr et al 2002). Although it has not been definitively shown that TH-positive neurons in the cochlea fall within this bifurcating class of neurons, Niu et al (2004) argue that the dense TH staining they previously observed in the cochlea (Niu and Canlon 2002) is clearly consistent with bifurcating distribution given the small number of TH-positive neurons in the LSO.…”
Section: Figmentioning
confidence: 94%
“…MOC dendrites are extensive (Adams 1983;White and Warr 1983;Osen et al 1984;Vetter and Mugnaini 1992;Warr et al 2002;Sánchez-González et al 2003). The remaining panels show averaged staining for two knockouts and two wild types in B medial edge, C dorsal edge, D lateral edge, and E core.…”
Section: Oc Somata and Dendritesmentioning
confidence: 99%